APPLICATION OF FULL COSTING METHOD FOR PRODUCTION COST DETERMINATION IN CULINARY MSMES - Nur Azizah (COMPETITIVE, 2026)
Accurate cost of production information is essential for determining appropriate selling prices and supporting Accurate production cost information is essential for determining appropriate selling prices and supporting managerial decision-making in Micro, Small, and Medium Enterprises (MSMEs). However, many culinary MSMEs still apply simplified costing practices by considering only direct costs and excluding manufacturing overhead, resulting in inaccurate production cost calculations. This study aims to analyze the application of the Full Costing method in determining production costs in a culinary MSME. A qualitative case study approach was employed, with data collected through observation, interviews, and documentation. The findings show that the enterprise initially calculated production costs based only on direct materials, direct labor, and gas expenses, while excluding electricity, water, equipment depreciation, and indirect material costs. After applying the Full Costing method, the total production cost increased from IDR 2,244,000 to IDR 2,669,000, representing an increase of approximately 18.9%. Consequently, the unit production cost increased from IDR 7,500 to IDR 9,000 per unit. The increase was mainly caused by the inclusion of previously unallocated manufacturing overhead costs. These findings demonstrate that the Full Costing method provides a more comprehensive basis for production cost determination and supports more accurate pricing decisions, cost control, and managerial planning. This study provides practical insights into improving cost information systems in culinary MSMEs.